2018
DOI: 10.1186/s40425-018-0477-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune-checkpoint inhibitor plus chemotherapy versus conventional chemotherapy for first-line treatment in advanced non-small cell lung carcinoma: a systematic review and meta-analysis

Abstract: BackgroundImmune-checkpoint inhibitors plus chemotherapy are emerging as effective first-line treatment in advanced non-small-cell lung carcinoma (NSCLC), but little is known about the magnitude of benefits and potential clinical predictors.MethodsWe performed a meta-analysis of randomized trials that compared PD-1/PD-L1 inhibitor plus chemotherapy with chemotherapy in first line of treatment for advanced NSCLC. The outcomes included progression-free survival (PFS), overall survival (OS), objective response ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 44 publications
4
87
1
4
Order By: Relevance
“…The third question is whether additional ICIs to the first‐line chemotherapy is necessary for patients with low or negative expression for PD‐L1. Previous studies have shown that the synergistic activity and acceptable safety profile could be observed by the combination of checkpoint inhibitors and chemotherapy in the first‐line treatment of advanced NSCLC . With the inclusion of two recent studies, our study drew consistent conclusion that compared with standard chemotherapy, the combination of chemotherapy and ICIs, regardless of atezolizumab or pembrolizumab could acquire significant benefits in mOS, OSR1y, mPFS, PFSR6m, PFSR1y, and ORR for PD‐L1 unselected patients in spite of higher incidence of grade ≥ 3 TRAEs.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The third question is whether additional ICIs to the first‐line chemotherapy is necessary for patients with low or negative expression for PD‐L1. Previous studies have shown that the synergistic activity and acceptable safety profile could be observed by the combination of checkpoint inhibitors and chemotherapy in the first‐line treatment of advanced NSCLC . With the inclusion of two recent studies, our study drew consistent conclusion that compared with standard chemotherapy, the combination of chemotherapy and ICIs, regardless of atezolizumab or pembrolizumab could acquire significant benefits in mOS, OSR1y, mPFS, PFSR6m, PFSR1y, and ORR for PD‐L1 unselected patients in spite of higher incidence of grade ≥ 3 TRAEs.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that the synergistic activity and acceptable safety profile could be observed by the combination of checkpoint inhibitors and chemotherapy in the first-line treatment of advanced NSCLC. 28,29 With the inclusion of two recent studies, our study drew consistent conclusion that compared with standard chemotherapy, the combination of chemotherapy and ICIs, regardless of atezolizumab or pembrolizumab could acquire significant benefits in mOS, OSR1y, mPFS, PFSR6m, PFSR1y, and ORR for PD-L1 unselected patients in spite of higher incidence of grade ≥ 3 TRAEs. When stratified by PD-L1 expression, patients with negative PD-L1 expression can further benefit from combination therapy in mOS, mPFS, and ORR, regardless of atezolizumab or pembrolizumab.…”
Section: Discussionmentioning
confidence: 57%
“…Fortunately, the development of immunotherapy challenged the management of treatment-related toxic effects. Like the prior study, ICI drugs were overall less toxic than chemotherapy especially in monotherapy, and combining an ICI with chemotherapy increased the rate of grade 3 or worse severity TRAEs [49,50]. Although combined therapy resulted in significantly longer overall survival and progression-free survival than chemotherapy, its cytotoxicity also improved, which should not be underestimated [51].…”
Section: Discussionmentioning
confidence: 65%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] However, severe and dose-limiting AEs were significantly greater for chemoimmunotherapy versus chemotherapy, with risk ratios (RRs) of 1.14 (95% CI 1.04-1.26) and 1.29 (95% CI 1.01-1.60) for grade 3-5 AEs and treatment discontinuation, respectively. 33 The combination chemoimmunotherapy also had higher rates of any-grade irAEs (RR 2.37, 95% CI 1.98-2.84) and grade 3-5 irAEs (RR 3.71, 95% CI 2. 63-5.24).…”
Section: Treatment Selectionmentioning
confidence: 95%
“…Interim PFS and OS results are promising for squamous NSCLC, whereas the OS end point for nonsquamous NSCLC was not met (Table ). A meta‐analysis of six randomized trials in 3144 patients with aNSCLC supports the results of the individual trials, showing improved PFS (HR 0.63, 95% CI 0.58–0.68), OS (HR 0.68, 95% CI 0.53–0.87), and ORR (OR 1.56, 95% CI 1.29–1.89) for first‐line anti‐PD1/PD‐L1 agents (pembrolizumab, atezolizumab, or nivolumab) plus chemotherapy compared with chemotherapy . This meta‐analysis also found that combination chemotherapy plus PD‐1 inhibitor (e.g., pembrolizumab) may be more efficacious than chemotherapy plus PD‐L1 inhibitor (e.g., atezolizumab), with OS HRs of 0.56 (95% CI 0.47–0.67) and 0.85 (95% CI 0.68–1.07), respectively, compared with chemotherapy.…”
Section: Treatment Selectionmentioning
confidence: 99%